The Evolution of Ancient Urban Defense Spaces in Northwest China During the Song–Ming Period - Tuo, Xiaolong; Li, Zhe (International Planning History Society Proceedings, 2022)
Based on the historical geographic database of the cities subordinated to the Ming Great Wall defense system and the Northern Song fortress defense system built by the research team, the history of military settlements in northwest China and their urban defense structure were traced. A comparative analysis of the spatial characteristics of urban defense planning during the Song and Ming Dynasties using settlement morphology data revealed significant differences in urban defense planning in the two eras. Focusing on typical urban settlements that span two historical periods and have continued into the present time, we analyzed continuous space-time slices of ancient urban defense spaces and explored their historical causes using ancient urban maps, local chronicles, and aerial photographs. Finally, the historical evolution sequence of ancient urban defense spaces was determined.